FEA Modelling of Externally-Strengthened Concrete Beam with CFRP Plates Under Flexural Test - Ahmad, Mohd Hilton; Maulana, Malik Ridwan; Mansor, Hazrina (International Journal of Integrated Engineering, 2022)
This study concentrates on FEA modelling of concrete beam strengthened with externally bonded CFRP lates under bending by using Traction Separation Law (TSL) as constitutive law to require maximum cohesive stress and fracture energy values. The FEA models were developed following experimental work reported by Al-Rousan et al. and Ding et al. Combination of two numerical techniques were adopted, i.e., Extended Finite Element Method (XFEM) and Cohesive Zone Method (CZM) assigned within cracked beam region and adhesive layer respectively. The consistence of FEA beam deformations to capture debonding failure as seen during experimental observations and load-displacement was evaluated accordingly. Additionally, combination of XFEM-CZM techniques provides good strength predictions with experimental dataset. It is clearly shown that the failure mode exhibited are determined by testing method, CFRP width and CFRP length. CFRP sheets provides a significant contribution to concrete ductility, which is noticeable in longest CFRP sheet. All testing series were examined, the discrepancies of less than 25% were found. Note that current approach used calibrated fracture energy values from similar concrete grade and CFRP plates, however better prediction can be produced if fracture energy values were independently determined from experimental set-up.